Internet of things (IoT) for optimum bus infrastructure - Kadzimu, Tapiwa (Midlands State University, 2019)
Rapid population growths or rural to urban migration and importation of small cheap private cars (mishikashika) has brought a lot of disarray in the public transport sector resulting n increased accidents ,traffic jams and inefficient transportation solutions in most major cities. The traditionally safer bus system is now underutilized and also ne sprouting illegal suburbs which are densely populated are being poorly serviced in terms of transport systems .this project seeks to bring an efficient solution for bus/transport allocation which is based on demand and fluctuations in demand during the whole day .it uses cameras and computer algorithms based on the open cv library suites to check bus stop status and alert the transport managers on which routes to prioritise as they can see the traffic profiles of different bus stops .computer learning ,human recognition and detection are the main concepts that are employed by this project to meet its objectives.